Development of Inulin-Enriched Honey Powder for Further Application in Prebiotic Biscuits - Jaya, Firman; Eka Radiati, Lilik; Setyo Prayogi , Heni; Masyithoh, Dewi; Agustini, Dini; Parlan (Jurnal Ilmu-Ilmu Peternakan, 2024)
Maltodextrin has the drawback of increasing the glycemic index (GI), which is considered healthy during the digestion process. The incorporation of inulin, a prebiotic agent, addresses these issues while offering additional health benefits. This study aimed to characterize inulin-enriched honey powder produced via spray drying with varying ratios (100%, 75%, 50%, and 25%) of inulin and maltodextrin as carriers for potential application as a sugar substitute for prebiotic biscuit formulations. Chemical properties, including pH, moisture content, hydroxymethylfurfural (HMF) content, diastase activity, and the sugar profile, were analysed. The results revealed that formulations containing 50% inulin presented optimal characteristics, such as a balanced pH, minimal HMF levels, and favourable sugar profiles (e.g., glucose, maltose, fructose-to-glucose and glucose-to-moisture ratios). These findings suggest that inulin-enriched honey powder with balanced carrier ratios could serve as an innovative sugar substitute, contributing to the development of healthier prebiotic biscuits. Future studies should explore functional properties, including the prebiotic potential of inulin-enriched honey powder, which impacts biscuit rheology and consumer acceptability.